PENGADAAN TANAH UNTUK SIAPA, PENIADAAN TANAH DARI SIAPA: PENGADAAN TANAH, ALOKASI TANAH, DAN KONFLIK AGRARIA - Amien Tohari (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2014)
The paper is aimed at discussing whether the policy of land acquisition can become a scheme of agrarian conflictsolution. Seen from the land acquisition as a practice of conflict solution, the paper is directly focused on conflict of agrarian context,that is whether the land acquisition can be an alternative solution scheme which can be used to solve the agrarian conflict. Thepaper wants to state that: first, the land acquisition is not intended as a scheme to solve the problem, second, the policy is a doubleblade knife that is acquisition and at the same time it is also the abolishment, third, the policy of land acquisition is intended tohold the infrastructural building, fourth,- through the agrarian conflict at Musi Banyuasin, the paper showed that the absence of landacquisition policy or land allocation for the society resulted unresolvable conflict.Keywords: land acquisition policy, conflict, unresolvable